Identifying plasma exosome antigens as a potential diagnostic biomarker for tuberculosis disease - Yan Jiang; Li Yan; Baoru Zhou; Jianming Hong; Huixing Tan; Xiaonan Li; Yong Wang (BMC Infectious Diseases)
Abstract Background Exosome is a small extracellular vesicle with a diameter of 30 to 150 nm that is secreted by cells. Mtb and other bacteria can also secrete extracellular vesicles, which carry characteristics and information about the pathogen. Here, we compare the concentration of exosomes and the Mtb antigen in exosomes of tuberculosis patients aiming to evaluate whether exosomes can be used as diagnostic markers of tuberculosis at different stages. Methods Plasma exosomes were extracted from healthy individuals, the patients with active TB and latent TB, Rehabilitation patients. The concentration and diameter of exosomes from different groups were detected using NTA. The antigen Ag85A, MPT64, CFP-10 of Mtb in exosomes was detected by ELISA. The area under the curve (AUC) was used to model the associations between exosomal Mtb Antigens and tuberculosis. Results We found that MPT64, Ag85A and CFP-10 levels were significantly higher in active and latent patients than in healthy and recovered patients. And he results shown the AUC for patients with active TB was 0.97 for MPT64, 1.0 for Ag85A, and 0.94 for CFP-10; for patients with latent TB, the AUC was 0.86 for MPT64, 0.98 for Ag85A, and 0.83 for CFP-10. Conclusion Levels of MPT64, Ag85A and CFP-10 were significantly up-regulated in plasma exosomes from TB patients and latent patients, and the AUC values of all three antigens predicting TB were higher than 0.9. This finding suggests that the three Mtb antigens in plasma exosomes were reliable diagnostic markers for TB.